Residual life prediction of defected Polypropylene Random copolymer pipes (PPR) - Abderazzak Ouardi; Fatima Majid; Nadia Mouhib; Mohamed Elghorba (Fracture and Structural Integrity)
The polypropylene random copolymer (PPR) is a thermoplastic material generally used for the transport of water under pressure, especially hot water. PPR pipes are exposed to severe conditions in terms of pressure and temperature, hence the need to characterize their fracture behavior in order to avoid the design risks. Sudden overpressure is one of the most common problems in piping. It can affect the security of goods and the safety of people. In this context, we have performed tests of overpressures at the laboratory scale according to ASTM D1599 standard, on virgin and notched pipes, to characterize mechanically the fracture behavior of PPR pipes. Afterwards, we identify experimentally the evolution of their damage. The calculation of the damage, by experimental damage models, have led to determine the three stages of evolution of the damage, which are the initiation, the progression and the acceleration of it. Therefore, the concept of reliability is used to specify the critical life fraction relative to the notch depth (βc) of a defect modeled as an external longitudinal groove on the PPR pipe. A comparison of PPR and HDPE pipes damage and reliability has been done. Moreover, a theoretical reassessment of the damage level was done through a judicious adaptation of the theoretical model proposed by the unified theory. From the latter, we proved that theoretical and experimental results show good agreement and correlations.